Keynes the Keynesian: A Lakatosian Insight into Keynes’s ‘Probable’ Theoretical Contributions to Macroeconomics after 1937 - Muñoz, Jesús; Bonales, Joel (My University, 2008)
In this substantial new collection, esteemed Post-Keynesian scholars reassess the relevance of Keynes’s The General Theory to a broad array of topic areas, ranging from the environment, investment finance, exchange rates, and socialism, as well as inquiries into general Post-Keynesian theory.